If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + y) = 2(y + -7) (3 * 3 + y * 3) = 2(y + -7) (9 + 3y) = 2(y + -7) Reorder the terms: 9 + 3y = 2(-7 + y) 9 + 3y = (-7 * 2 + y * 2) 9 + 3y = (-14 + 2y) Solving 9 + 3y = -14 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 9 + 3y + -2y = -14 + 2y + -2y Combine like terms: 3y + -2y = 1y 9 + 1y = -14 + 2y + -2y Combine like terms: 2y + -2y = 0 9 + 1y = -14 + 0 9 + 1y = -14 Add '-9' to each side of the equation. 9 + -9 + 1y = -14 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = -14 + -9 1y = -14 + -9 Combine like terms: -14 + -9 = -23 1y = -23 Divide each side by '1'. y = -23 Simplifying y = -23
| Y=7.50x-5 | | 5.004562837%= | | 9283838929=028833939 | | -4(t-4)+8=9t-1 | | 2x+5=-2-5x | | 2+7e=23 | | 3(a-5)-10=2(2a+1)+8a | | 4s+13t+7s+3t+16= | | G(x)=3f(x-4) | | 18-3(x+2)=9x+1 | | -8x-39=-8(x+5)+1 | | (2xc)+5=11 | | -2x+1=-x+9 | | -6+4n=-30 | | 55-2s=9 | | 8(n+1)=6n+22 | | n+(n+2)+3n=12 | | 12+4x=6x-4 | | 34.87=7g+3.51 | | -2-3x=3+c | | 6(2x-3)=3(3x-7) | | -5(t-3)+7=6t-9 | | 10+2(x-3)=18 | | (6x+4)10x= | | 60+60+[4x-80]=180 | | 7(x-2)+7x=5(x+4)-7 | | 7x+y=215 | | y-1=0.33(x+3) | | xlogM+2logM-3xLogN+4LogN=0 | | 28.3=-12w | | 3+6x=43-4x | | 0.12x+0.9(x-2)=0.01(2x-3) |